Konsep Maslahah dalam Perspektif KH. Ma. Sahal Mahfudh - Imam Bukhori (FALASIFA : Jurnal Studi Keislaman, 2017)
ABSTRACT The resulting decisions also have no significant influence in some aspects. This can be understood, for example, through the tradition of polar al-mu'tabarah use as a tool in solving contemporary problems. This tradition is firmly held by pesantren and NU circles in Indonesia, even though these two Indonesian Islamic entities have begun to adopt the system of manhajiy, no longer qawly, as some of the past. The use of medieval fiqh books as a reference in the settlement of social problems is considered to have substantive weaknesses, especially in terms of differences in time, sociological, psychological, and cultural. Keyword: The concept of maslahah, KH perspective. MA. Sahal Mahfudh